Arabidopsis Basic Helix-Loop-Helix 34 (bHLH34) Is Involved in Glucose Signaling through Binding to a GAGA Cis-Element - Min, Ji-Hee; Ju, Hyun-Woo; Yoon, Dayoung; Lee, Kyeong-Hwan; Lee, Sungbeom; Kim, Cheol S. (Frontiers in Plant Science, 2017)
The modulation of glucose (Glc) homeostasis and signaling is crucial for plant growth and development. Nevertheless, the molecular signaling mechanism by which a plant senses a cellular Glc level and coordinates the expression of Glc-responsive genes is still incompletely understood. Previous studies have shown that Arabidopsis thaliana plasma membrane Glc-responsive regulator (AtPGR) is a component of the Glc-responsive pathway. Here, we demonstrated that a transcription factor bHLH34 binds to 5′-GAGA-3′ element of the promoter region of AtPGR in vitro, and activates beta-glucuronidase (GUS) activity upon Glc treatment in AtPGR promoter-GUS transgenic plants. Gain- and loss-of-function analyses suggested that the bHLH34 involved in the responses to not only Glc, but also abscisic acid (ABA) and salinity. These results suggest that bHLH34 functions as a transcription factor in the Glc-mediated stress responsive pathway as well as an activator of AtPGR transcription. Furthermore, genetic experiments revealed that in Glc response, the functions of bHLH34 are different from that of a bHLH104, a homologue of bHLH34. Collectively, our findings indicate that bHLH34 is a positive regulator of Glc, and may affect ABA or salinity response, whereas bHLH104 is a negative regulator and epistatic to bHLH34 in the Glc response.